‘STEPNCFBUoA’ - An Advanced Manufacturing Control System based on STEP-NC and FB enabled technology - Minhat, Mohamad; Xu, Xun (2010)
The vital requirement for manufacturing world is to take knowledge of technologies along with process and this requires information and database of product as well as process data. For some time now product data model has to be transferred among CAD, CAE, CAPP, CAM system to CNC machines. STEP-NC standards and product data models have given a very wide opportunity and future product of another controller which will be taking a big role in replacing G and M codes in a future. This research describes a framework of a STEP-NC controller which is trying to integrate the system element, information and product data along CAx system to CNC machines. The STEP-NC controller with the new specification, standards and development together with appropriate interface and language, will give huge implications and promise to connect CNCs through the internet and restructure the CNC machining process. It also offers the opportunity to realize interoperable CNC machining and facilitate the use of information bi-directional stream in the chain. This research work will also incorporate function blocks that are an emerging IEC standard (IEC 61499) for distributed industrial processes, control systems design and the framework is explaining how to implement the controller.